2021
DOI: 10.1109/access.2021.3076356
|View full text |Cite
|
Sign up to set email alerts
|

Case Studies on the Use of Sentiment Analysis to Assess the Effectiveness and Safety of Health Technologies: A Scoping Review

Abstract: A health technology assessment (HTA) is commonly defined as a multidisciplinary approach used to evaluate medical, social, economic, and ethical issues related to the use of a health technology in a systematic, transparent, unbiased, robust manner. To help inform HTA recommendations, the surveillance of social media platforms can provide important insights to the clinical community and to decision makers on the effectiveness and safety of the use of health technologies on a patient. A scoping review of the pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Our findings are consistent with the recommendations from other recent reviews (21; 22), which concluded that "the outcomes of these applications should be considered exploratory" (in the context of sentiment analysis) (22) but also suggested that the current body of research should be used to inform further development of more structured and consistent methods as well as guidance (21). Therefore, a second, separate output from this project is an initial guidance or framework to support future producers and users of Social Media Research in quality assurance published in this same journal (17).…”
Section: Social Media Research Methodssupporting
confidence: 92%
“…Our findings are consistent with the recommendations from other recent reviews (21; 22), which concluded that "the outcomes of these applications should be considered exploratory" (in the context of sentiment analysis) (22) but also suggested that the current body of research should be used to inform further development of more structured and consistent methods as well as guidance (21). Therefore, a second, separate output from this project is an initial guidance or framework to support future producers and users of Social Media Research in quality assurance published in this same journal (17).…”
Section: Social Media Research Methodssupporting
confidence: 92%
“…Social media data analysis has been applied in various health research areas, such as, disease surveillance, and health outcomes research [8][9][10] . Safety outcomes, in particular, have been extensively studied [8][9][10], and patient reports of ADEs are found abundantly within this content-rich resource [11].…”
Section: Introductionmentioning
confidence: 99%
“…Social media data analysis and monitoring have been investigated for its application in health research including health outcomes research, disease surveillance, and patient perspectives [8][9][10]. However, the most commonly studied outcome is that of safety [8][9][10]. Indeed, social media has been identified as a content-rich resource of patient reports of ADEs [11].…”
Section: Introductionmentioning
confidence: 99%